Ovarian neoplasms and pregnancy - Vidal Amat y León, Jorge (2015)
One group of 50 patients with diagnosis of ovarian neoplasia in different periods of pregnancy and that required emergency surgery for complications. Hormonal treatment is shown to compensate for the absence of corpus luteum in the first weeks of pregnancy and two cases of ovarian malignancy associated with pregnancy are presented, showing their treatment and evolution.